Tyrosyl-DNA phosphodiesterase 2 (Tdp2) repairs DNA-protein crosslinks and protects against double strand breaks in vivo - Anticevic, Ivan; Otten, Cecile; Popovic, Marta (Frontiers in Cell and Developmental Biology, 2024)
DNA-protein crosslinks pose a significant challenge to genome stability and cell viability. Efficient repair of DPCs is crucial for preserving genomic integrity and preventing the accumulation of DNA damage. Despite recent advances in our understanding of DPC repair, many aspects of this process, especially at the organismal level, remain elusive. In this study, we used zebrafish as a model organism to investigate the role of TDP2 (Tyrosyl-DNA phosphodiesterase 2) in DPC repair. We characterized the two tdp2 orthologs in zebrafish using phylogenetic, syntenic and expression analysis and investigated the phenotypic consequences of tdp2 silencing in zebrafish embryos. We then quantified the effects of tdp2a and tdp2b silencing on cellular DPC levels and DSB accumulation in zebrafish embryos. Our findings revealed that tdp2b is the main ortholog during embryonic development, while both orthologs are ubiquitously present in adult tissues. Notably, the tdp2b ortholog is phylogenetically closer to human TDP2. Silencing of tdp2b, but not tdp2a, resulted in the loss of Tdp2 activity in zebrafish embryos, accompanied by the accumulation of DPCs and DSBs. Our findings contribute to a more comprehensive understanding of DPC repair at the organismal level and underscore the significance of TDP2 in maintaining genome stability.